2021
DOI: 10.1038/s41419-021-04292-5
|View full text |Cite
|
Sign up to set email alerts
|

CHD8 safeguards early neuroectoderm differentiation in human ESCs and protects from apoptosis during neurogenesis

Abstract: The chromatin remodeler CHD8, which belongs to the ATP-dependent chromatin remodelers CHD family, is one of the most high-risk mutated genes in autism spectrum disorders. However, the role of CHD8 in neural differentiation and the mechanism of CHD8 in autism remains unclear, despite there are a few studies based on the CHD8 haploinsufficient models. Here, we generate the CHD8 knockout human ESCs by CRISPR/Cas9 technology and characterize the effect of loss-of-function of CHD8 on pluripotency maintenance and li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…The cell cycle analysis was performed according to a previous work 64 . In brief, one million single cells were fixed in 75% ethanol at 4 °C overnight.…”
Section: Methodsmentioning
confidence: 99%
“…The cell cycle analysis was performed according to a previous work 64 . In brief, one million single cells were fixed in 75% ethanol at 4 °C overnight.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies on Chd8 -mutant mice and human neurons suggested multiple mechanisms that may underlie CHD8-related brain deficits ( Sugathan et al, 2014 ; Cotney et al, 2015 ; Wang et al, 2015 ; Breuss and Gleeson, 2016 ; Durak et al, 2016 ; Katayama et al, 2016 ; Gompers et al, 2017 ; Platt et al, 2017 ; Wang et al, 2017 ; Andreae and Basson, 2018 ; Jung et al, 2018 ; Suetterlin et al, 2018 ; Wade et al, 2018 ; Xu et al, 2018 ; Zhao et al, 2018 ; Hulbert et al, 2020 ; Jimenez et al, 2020 ; Sood et al, 2020 ; Cherepanov et al, 2021 ; Ding et al, 2021 ; Ellingford et al, 2021 ; Hurley et al, 2021 ; Kawamura et al, 2021 ; Kweon et al, 2021 ; Weissberg and Elliott, 2021 ; Chen et al, 2022 ; Coakley-Youngs et al, 2022 ; Dong et al, 2022 ; Haddad Derafshi et al, 2022 ; Jimenez et al, 2022 ; Kerschbamer et al, 2022 ; Lee et al, 2022 ; Paulsen et al, 2022 ; Thudium et al, 2022 ; Tu et al, 2022 ; Villa et al, 2022 ; Yu et al, 2022 ; Hayot et al, 2023 ). However, mechanisms underlying the male–female differences in CHD8-related ASD are poorly understood ( Jung et al, 2018 ; Cherepanov et al, 2021 ; Yu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…3 C). Furthermore, ectoderm differentiation from hPSCs [ 25 , 26 ] in TFAM knockout group expressed much lower SOX1 (ectoderm) ( Fig. 3 D).…”
Section: Resultsmentioning
confidence: 99%